Analisis Multi-Criteria Decision Making (MCDM) pada Pengambilan Keputusan Pemilihan Vendor dengan Metode Analytical Hierarchy Process (AHP) - Hakim, Arham Nashiruddin; Setiawan, Danang (Jurnal Studi Multidisiplin Qomaruna, 2025)
The high level of competition in the coal mining sector demands that companies optimize their strategies, technologies, and resources, including selecting the right vendors and partners, to survive and achieve maximum profit with minimal cost. The objective of this research is to select the best vendor for the procurement of wastewater quality monitoring at PT XYZ. The method used is the Analytic Hierarchy Process (AHP). There are six criteria used in the vendor selection process: quality, cost, delivery, environment, safety, and morale. The weight of each criterion was obtained through a pairwise comparison process conducted by seven experts in supply management and occupational safety, using Saaty's scale. The consistency of judgments was verified using the Consistency Ratio (CR) calculation, and all comparison matrices met the CR threshold. Among five suppliers evaluated, Supplier 4 (coded as A4) emerged as the best vendor, achieving the highest overall weight across all criteria.